Pengaruh Interval Training Terhadap Volume Oksigen Maksimal Pada Kegiatan Ekstrakurikuler Futsal - hartati, Hartati (Journal of Sport Science and Education, 2019)
ABSTRACT: The purpose of this study was to determine the effect of interval training on physical endurance in futsal extracurricular activities at SMA Negeri 6 Palembang. This research is an experimental study with the design of quasi experimental design of nonequivalent control group design. The population in this study were 60 people, and the sample in this study was the same as the population, so this study was also referred to as population research. The sampling technique in this study used a systematic sampling technique with an ordinal pairing system, in which samples were divided into two groups, the experimental group and the control group. The experimental group were given interval training treatment while the control group is the group that is not treated. The instrument used in this research is multistage fitness test (mft) or called a bleef test. This test is used in the initial test (pretest) and final test (posttest) which aims to determine the level of predictions of the VO2Max of students, obtained findings from this research is the results of the average VO2Max experimental group at pretest were 34.0 and posttest 39.5, and the results of the control group VO2Max at pretest were 33.8 and posttest 34.0. Then, after testing the results of the data analyzed using statistical data analysis techniques t test with a significant level (Î± = 0.05). Based on the results of the research tcount = 16,05 and ttable = 1.675. Therefore the hypothesis in this study received is that there is an effect of interval training on physical endurance in futsal extracurricular activities at SMA Negeri 6 Palembang.Key words: Interval training, physical endurance, futsal, students.Â